Lubricating agent for wood-plastic composite material for vehicle and preparation method of lubricating agent
By using maleic anhydride grafted lubricants composed of raw materials such as polyethylene, silicone powder, nanosilica in situ modified bamboo fiber powder and polypropylene wax, the processing performance of PP wood-plastic composite materials under large wood powder is solved. The problem of poor and poor mechanical properties has achieved the effect of improving the compatibility and mechanical properties of wood powder with PP.
Patent Information
- Application Number
- CN202411780525.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-02-18
AI Technical Summary
The existing PP wood-plastic composite materials have poor processing performance under large wood powder usage and are not ideal in mechanical properties, making it difficult to meet the strict performance requirements of automotive interiors.
Lubricants composed of maleic anhydride grafted polyethylene, silicone powder, nanosilica in-situ modified bamboo fiber powder and polypropylene wax are used to improve wood powder and interface modifier. PP compatibility, improve processing and mechanical properties.
It effectively improves the compatibility of wood powder and PP, improves the processing performance and mechanical properties of PP wood-plastic composite materials, and can meet the strict requirements of automotive interiors.
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lubricants, and in particular to a lubricant for a wood-plastic composite material for a vehicle and a preparation method thereof. Background Art
[0002] Wood-plastic composites are a new type of composite material made by adding wood powder, a natural fiber, to the thermoplastic resin as the base material. As a new material, wood-plastic composites not only have the advantages of wood products and plastic products, but also can use wood powder prepared from waste materials from wood product processing as raw materials, which can effectively reduce environmental pollution and save resources. Among the thermoplastic resin matrices used in wood-plastic composites, polypropylene (PP) has high hardness, bending fatigue resistance, and chemical resistance, and is low in cost and is the most widely used. Wood-plastic composites with PP as the base material are widely used in automotive interior parts.
[0003] The existing PP wood-plastic composite materials have poor compatibility due to the hydrophilicity of the wood component and the hydrophobicity of PP. Although the existing technology can solve the problem of poor compatibility between the two by modifying the wood component or adding lubricants during the processing of the wood-plastic composite materials, if the proportion of wood components in PP wood-plastic composite materials is large, the melt viscosity of the composite system will still increase, the flow performance will deteriorate, and even melt fracture and flow instability will occur, which will lead to the problem of reduced mechanical properties of the wood-plastic composite products.
[0004] With the development of the automobile industry, the requirements for the apparent quality of automobile interior products are constantly increasing. In the PP wood-plastic composite materials used, the proportion of wood powder usually exceeds 50% or even higher, which makes the wood-plastic products have an apparent quality similar to that of composite wood products. However, after adding such a large amount of wood powder, whether it is the hydrophobic modification of wood powder in the existing technology or the use of existing lubricants such as stearic acid, amide, organic wax and composite lubricant, the overall mechanical properties of the PP wood-plastic composite materials are not ideal, and it is difficult to meet the increasingly stringent technical requirements for various performance requirements of current automobile interiors. Summary of the invention
[0005] In order to solve at least one of the above technical problems, a lubricant product is developed for PP wood-plastic composite materials with a wood powder content exceeding 50%, which can effectively improve the compatibility between the wood component and polypropylene in the above material, and effectively solve the problems of poor processing performance of PP wood-plastic composite materials and unsatisfactory product mechanical properties when a large amount of wood powder is used. The present application provides a lubricant for automotive wood-plastic composite materials and a preparation method thereof.
[0006] On the one hand, the present application provides a lubricant for a wood-plastic composite material for a vehicle, wherein the mass ratio of the raw material components of the lubricant is: 24 to 32 parts of maleic anhydride grafted polyethylene, 8 to 10 parts of silicone powder, 30 to 40 parts of nano-silicon dioxide in-situ modified bamboo fiber powder, and 20 to 40 parts of polypropylene wax; the particle size of the nano-silicon dioxide in-situ modified bamboo fiber powder is 80 to 200 meshes, and the grafting rate of the maleic anhydride grafted polyethylene is 0.4 to 0.6%.
[0007] Optionally, the mass proportion of the raw material components of the lubricant is: 28-30 parts of maleic anhydride grafted polyethylene, 8-10 parts of silicone powder, 32-36 parts of nano-silicon dioxide in-situ modified bamboo fiber powder, and 28-30 parts of polypropylene wax.
[0008] Optionally, the method for preparing the nano-silicon dioxide in-situ modified bamboo fiber powder comprises the following steps: S1-1, placing the original bamboo fiber powder in a sodium hydroxide solution with a concentration of 4-8%, soaking for more than 4 hours, filtering out the sodium hydroxide solution, washing the obtained original bamboo fiber powder with distilled water until there is no residual sodium hydroxide, and then placing it in a constant temperature drying oven to dry to constant weight, to obtain alkali-treated bamboo fiber powder; S1-2, treating the alkali-treated bamboo fiber powder obtained in step S1-1 by a sol-gel method to generate nano-silicon dioxide on its surface in situ, and then drying it in a constant temperature drying oven to constant weight to obtain nano-silicon dioxide in situ modified bamboo fiber powder.
[0009] Further optionally, in step S1-1, the drying temperature is 80-100°C.
[0010] Further optionally, in the step S1-1, the dried alkali-treated bamboo fiber powder needs to be pulverized to disperse the agglomerated alkali-treated bamboo fiber powder.
[0011] Further optionally, in step S1-2, the sol-gel treatment includes the following steps: first, preparing a reaction solution, mixing tetraethyl orthosilicate, methyltriethoxysilane, ethanol, acetic acid and water in a volume ratio of 1:1:1:0.01:0.1 to prepare a reaction solution; then, mixing the alkali-treated bamboo fiber powder with the reaction solution in a mass ratio of 1:10, ultrasonically dispersing, standing for 1 to 2 hours, filtering out and standing at room temperature for 3 to 5 days.
[0012] Further optionally, in step S1-2, the drying temperature is 120-125°C.
[0013] Optionally, the raw material components of the lubricant also include an antioxidant, and the added amount of the antioxidant is 1 to 3 parts.
[0014] On the other hand, the present application provides a method for preparing the above-mentioned lubricant for automotive wood-plastic composite materials, comprising the following steps: S1. According to the above steps, prepare nano-silicon dioxide in-situ modified bamboo fiber powder; S2. Accurately weigh the raw materials in the formula, place them in a high-speed mixer and stir and mix them thoroughly to obtain a mixture; S3, adding the mixed material obtained in step S2 into an extruder, and obtaining a lubricant for a wood-plastic composite material for a vehicle through extrusion and granulation.
[0015] Optionally, in step S3, the temperature of each section of the extruder is controlled within 165°C.
[0016] In summary, the present invention includes at least one of the following beneficial technical effects: 1. This application uses modified bamboo fiber powder and other lubricating components, with modified bamboo fiber powder and polypropylene wax as the main lubricating components and maleic anhydride grafted polyethylene as an interface modifier, and the obtained lubricant can improve the compatibility of wood powder and PP.
[0017] 2. In this application, the modified bamboo fiber powder and maleic anhydride grafted polyethylene are compounded to effectively improve the compatibility of wood powder and PP. When the lubricant is processed in the PP wood-plastic composite material, the modified bamboo fiber powder can be mixed into the PP wood-plastic composite material more evenly, which can greatly improve the various mechanical properties of the PP wood-plastic composite material product.
[0018] 3. The preparation method of the present application obtains a granular lubricant by mixing raw materials, coordinating extrusion and granulation steps. The granular lubricant not only has good storage stability, but also can be easily added during the processing of PP wood-plastic composite materials. DETAILED DESCRIPTION
[0019] The present application is further described in detail below in conjunction with embodiments.
[0020] The present application designs a lubricant for a wood-plastic composite material for a vehicle. The mass proportion of each raw material component of the lubricant is: 24-32 parts of maleic anhydride grafted polyethylene, 8-10 parts of silicone powder, 30-40 parts of nano-silicon dioxide in-situ modified bamboo fiber powder, and 20-40 parts of polypropylene wax; the particle size of the nano-silicon dioxide in-situ modified bamboo fiber powder is 80-200 meshes, and the grafting rate of the maleic anhydride grafted polyethylene is 0.4-0.6%.
[0021] The method for preparing the lubricant of the vehicle wood-plastic composite material of the present application comprises the following steps: S1. Prepare nano-silicon dioxide in-situ modified bamboo fiber powder by using the specific preparation method of the present application; S2. Accurately weigh the raw materials in the formula, place them in a high-speed mixer and stir and mix them thoroughly to obtain a mixture; S3, adding the mixed material obtained in step S2 into an extruder, and obtaining a lubricant for a wood-plastic composite material for a vehicle through extrusion and granulation.
[0022] The lubricant of the automotive wood-plastic composite material of the present application is mainly used for processing automotive PP wood-plastic composite materials with wood powder content exceeding 50%. When the lubricant of the automotive wood-plastic composite material of the present application is used, the added amount accounts for about 10% of the total weight of the PP wood-plastic composite material.
[0023] Prior to this application, the lubricant for PP wood-plastic composite materials in the art generally adopts stearate, or wax lubricants such as paraffin wax and PE wax, or the composite lubricant thereof; and, in order to solve the compatibility problem, no new wood component is introduced into the lubricant.
[0024] However, although existing lubricants can improve the compatibility of wood powder and PP, when used in the processing of automotive PP wood-plastic composite materials with a wood powder content of more than 50%, due to the relatively higher wood powder content of this type of material, tiny gaps are likely to exist between PP and wood powder in the composite material products made by mixing PP and wood powder, resulting in poor mechanical properties of the product.
[0025] The technical solution of this application is designed based on the problems existing in the prior art; polyethylene wax lubricant and maleic anhydride grafted polyethylene interfacial modifier are used to achieve lubrication, and modified bamboo fiber powder is used as an auxiliary solubilizer to further improve the compatibility of wood powder and PP. After the modified bamboo fiber powder is added, its surface contains nano-silicon dioxide whiskers, which can be dispersed in the composite material, effectively fill the gaps, and thus effectively improve the overall mechanical properties of the composite material.
[0026] The following are preparation examples and embodiments of the present application: The sources of raw materials and equipment selections of the preparation examples and embodiments of this application are as follows: Raw bamboo fiber powder, particle size 80-200 mesh, was purchased from Jiangxi Ruimei Bamboo and Wood Technology Co., Ltd.; polypropylene wax was purchased from Wuhan Jiyesheng Chemical Co., Ltd.; maleic anhydride grafted polyethylene, grafting rate 0.5%, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; tetraethyl orthosilicate and methyltriethoxysilane were purchased from Sigma-Aldrich (Shanghai) Trading Co., Ltd.; silicone powder was purchased from Shanghai Jinghong Chemical Technology Co., Ltd.; antioxidant 1010 was purchased from BASF.
[0027] The following are preparation examples 1 to 4 of this application Preparation Example 1 The preparation of the nano-silicon dioxide in-situ modified bamboo fiber powder in this preparation example comprises the following steps: S1-1, mixing raw bamboo fiber powder and 4% sodium hydroxide solution in a mass ratio of 1:8, soaking for 4 hours, filtering out the sodium hydroxide solution, washing the obtained raw bamboo fiber powder with distilled water until the pH value of the washing waste liquid is neutral, and then placing it in a constant temperature drying oven, drying it at 80°C to constant weight, and crushing it with a pulverizer until the agglomerated powder is evenly dispersed to obtain alkali-treated bamboo fiber powder; S1-2, treating the alkali-treated bamboo fiber powder obtained in step S1-1 by a sol-gel method to generate nano-silicon dioxide on its surface in situ; specifically, firstly preparing a reaction solution with a volume ratio of 1:1:1:0.01:0.1 of ethyl orthosilicate, methyltriethoxysilane, ethanol, acetic acid and water; then, mixing the alkali-treated bamboo fiber powder with the reaction solution in a mass ratio of 1:10, ultrasonically dispersing for 30 minutes, standing for 1 hour, filtering out and standing at room temperature for 3 days to obtain modified bamboo fiber powder; S1-3, placing the modified bamboo fiber powder obtained in step S1-2 in a constant temperature drying oven, drying at 120° C. to constant weight, and crushing with a pulverizer until the agglomerated powder is evenly dispersed to obtain nano-silicon dioxide in-situ modified bamboo fiber powder.
[0028] Preparation Example 2 The preparation of the nano-silicon dioxide in-situ modified bamboo fiber powder in this preparation example comprises the following steps: S1-1, mixing raw bamboo fiber powder and 6% sodium hydroxide solution in a mass ratio of 1:10, soaking for 4 hours, filtering out the sodium hydroxide solution, washing the obtained raw bamboo fiber powder with distilled water until the pH value of the washing waste liquid is neutral, and then placing it in a constant temperature drying oven, drying it at 80°C to constant weight, and crushing it with a pulverizer until the agglomerated powder is evenly dispersed to obtain alkali-treated bamboo fiber powder; S1-2, treating the alkali-treated bamboo fiber powder obtained in step S1-1 by a sol-gel method to generate nano-silicon dioxide on its surface in situ; specifically, firstly preparing a reaction solution with a volume ratio of 1:1:1:0.01:0.1 of ethyl orthosilicate, methyltriethoxysilane, ethanol, acetic acid and water; then, mixing the alkali-treated bamboo fiber powder with the reaction solution in a mass ratio of 1:10, ultrasonically dispersing for 30 minutes, standing for 1 hour, filtering out and standing at room temperature for 3 days to obtain modified bamboo fiber powder; S1-3, placing the modified bamboo fiber powder obtained in step S1-2 in a constant temperature drying oven, drying at 120° C. to constant weight, and crushing with a pulverizer until the agglomerated powder is evenly dispersed to obtain nano-silicon dioxide in-situ modified bamboo fiber powder.
[0029] Preparation Example 3 The preparation of the nano-silicon dioxide in-situ modified bamboo fiber powder in this preparation example comprises the following steps: S1-1, mixing raw bamboo fiber powder and 8% sodium hydroxide solution in a mass ratio of 1:10, soaking for 4 hours, filtering out the sodium hydroxide solution, rinsing the obtained raw bamboo fiber powder with distilled water until the pH value of the rinsing waste liquid is neutral, and then placing it in a constant temperature drying oven, drying it at 100° C. to constant weight, and pulverizing it with a pulverizer until the agglomerated powder is evenly dispersed to obtain alkali-treated bamboo fiber powder; S1-2, treating the alkali-treated bamboo fiber powder obtained in step S1-1 by a sol-gel method to generate nano-silicon dioxide on its surface in situ; specifically, firstly preparing a reaction solution with a volume ratio of 1:1:1:0.01:0.1 of ethyl orthosilicate, methyltriethoxysilane, ethanol, acetic acid and water; then, mixing the alkali-treated bamboo fiber powder with the reaction solution in a mass ratio of 1:10, ultrasonically dispersing for 30 minutes, standing for 1 hour, filtering out and standing at room temperature for 3 days to obtain modified bamboo fiber powder; S1-3, placing the modified bamboo fiber powder obtained in step S1-2 in a constant temperature drying oven, drying at 125° C. to constant weight, and crushing with a pulverizer until the agglomerated powder is evenly dispersed to obtain nano-silicon dioxide in-situ modified bamboo fiber powder.
[0030] Preparation Example 4 The preparation of the nano-silicon dioxide in-situ modified bamboo fiber powder in this preparation example comprises the following steps: S1-1, mixing raw bamboo fiber powder and 8% sodium hydroxide solution in a mass ratio of 1:10, soaking for 4 hours, filtering out the sodium hydroxide solution, washing the obtained raw bamboo fiber powder with distilled water until the pH value of the washing waste liquid is neutral, and then placing it in a constant temperature drying oven, drying it at 85°C to constant weight, and crushing it with a pulverizer until the agglomerated powder is evenly dispersed to obtain alkali-treated bamboo fiber powder; S1-2, treating the alkali-treated bamboo fiber powder obtained in step S1-1 by a sol-gel method to generate nano-silicon dioxide on its surface in situ; specifically, firstly preparing a reaction solution with a volume ratio of 1:1:1:0.01:0.1 of ethyl orthosilicate, methyltriethoxysilane, ethanol, acetic acid and water; then, mixing the alkali-treated bamboo fiber powder and the reaction solution with a mass ratio of 1:10, ultrasonically dispersing for 30 minutes, standing for 2 hours, filtering out and standing at room temperature for 5 days to obtain modified bamboo fiber powder; S1-3, placing the modified bamboo fiber powder obtained in step S1-2 in a constant temperature drying oven, drying at 120° C. to constant weight, and crushing with a pulverizer until the agglomerated powder is evenly dispersed to obtain nano-silicon dioxide in-situ modified bamboo fiber powder.
[0031] The following are examples of this application All the examples in this application were prepared by the following method, which specifically includes the following steps: S1, selecting nano-silicon dioxide in situ modified bamboo fiber powder of a specific preparation example; S2. Accurately weigh the raw materials in the formula, place them in a high-speed mixer and stir and mix them thoroughly to obtain a mixture; S3, adding the mixture obtained in step S2 into an extruder, and obtaining a lubricant for a wood-plastic composite material for a vehicle through extrusion and granulation; The parameters of the twin-screw extruder were set as follows: screw speed 320 rpm, temperature of each section: zone 1 156°C, zone 2 162°C, zone 3 165°C, zone 4 165°C, zone 5 162°C.
[0032] The following are Examples 1 to 6 of this application Examples 1 to 6 of the present application all use the nano-silicon dioxide in-situ modified bamboo fiber powder prepared in Preparation Example 1. The composition ratios of each component of Examples 1 to 6 of the present application are shown in Table 1 below.
[0033] Table 1 Proportions of Examples 1 to 6 Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Maleic Anhydride Grafted Polyethylene 24 servings 28 servings 32 servings 28 servings 28 servings 30 servings Silicone powder 8 servings 9 servings 10 servings 8 servings 9 servings 10 servings Modified bamboo fiber powder 30 servings 35 servings 40 servings 32 servings 34 servings 36 servings Polypropylene wax 20 servings 30 servings 40 servings 28 servings 29 servings 30 servings The following are Examples 7 to 10 of this application The proportions of Examples 7 to 9 of the present application are exactly the same as those of Example 5 of the present application, except that the nano-silicon dioxide in-situ modified bamboo fiber powder uses the powders prepared in Preparation Examples 2 to 4, respectively.
[0034] Example 10 of the present application is basically the same as Example 9 of the present application, the only difference being that 2 portions of antioxidant are added to the raw materials.
[0035] Comparative Example 1 The present application uses a lubricant prepared by mixing maleic anhydride grafted polypropylene, zinc stearate and polypropylene wax in a mass ratio of 3:5:2 as comparative example 1 of the present application.
[0036] Comparative Example 2 This application uses the high-efficiency lubricant model YY20A produced by Kunshan Yayang Composite Materials Technology Co., Ltd. as comparative example 2.
[0037] Comparative Example 3 The difference between this comparative example and Example 10 is that an equal amount of polypropylene wax is used to replace the nano-silicon dioxide in-situ modified bamboo fiber powder.
[0038] Comparative Example 4 The difference between this comparative example and Example 10 is that an equal amount of maleic anhydride grafted polyethylene with a grafting rate of about 0.8% is used to replace the maleic anhydride grafted polyethylene with a grafting rate of about 0.5%.
[0039] Comparative Example 5 The difference between this comparative example and Example 10 is that an equal amount of the alkali-treated bamboo fiber powder obtained in step S1-1 of Preparation Example 4 is used to replace the nano-silicon dioxide in-situ modified bamboo fiber powder.
[0040] Performance Testing In the test experiment of this application, the PP wood-plastic composite board is prepared using the following ratio: 35 parts of PP raw material, 55 parts of wood powder, and 10 parts of lubricant; the wood powder uses poplar powder with a particle size of 80~100 mesh.
[0041] The plates used in the test experiments of this application were all prepared by a hot pressing process, and the hot pressing temperature was controlled at 170°C.
[0042] In the present application, lubricants of Examples 1 to 10 and Comparative Examples 1 to 5 are used to prepare plates according to the above-mentioned ratios and preparation methods. The prepared plates are numbered as Samples 1 to 10 and Comparative Samples 1 to 5, respectively.
[0043] The performance tests of the present application respectively tested the apparent quality, precipitation conditions and comprehensive mechanical properties of samples 1 to 10 and comparison samples 1 to 5.
[0044] 1) Appearance quality and precipitation According to the method described in GB∕T 24508-2020, the appearance quality and boiling water resistance of the board were tested. The test results are shown in Table 2 below.
[0045] Table 2 Performance test 1) Results table Appearance quality Boiling water resistant Sample 1 Smooth surface No change in appearance, no surface frost Sample 2 Smooth surface No change in appearance, no surface frost Sample 3 Smooth surface No change in appearance, no surface frost Sample 4 Smooth surface No change in appearance, no surface frost Sample 5 Smooth surface No change in appearance, no surface frost Sample 6 Smooth surface No change in appearance, no surface frost Sample 7 Smooth surface No change in appearance, no surface frost Sample 8 Smooth surface No change in appearance, no surface frost Sample 9 Smooth surface No change in appearance, no surface frost Sample 10 Smooth surface No change in appearance, no surface frost Comparative sample 1 Smooth surface No change in appearance, no surface frost Comparative sample 2 Smooth surface Slightly frosted surface Comparative sample 3 Smooth surface No change in appearance, no surface frost Comparative sample 4 Smooth surface No change in appearance, no surface frost Comparative sample 5 Smooth surface No change in appearance, no surface frost From the data in Table 2, it can be seen that the appearance quality of the plate samples prepared by using the lubricants of Examples 1 to 10 of the present application fully meets the requirements of the national standards, the boiling water resistance is also good, and no additives are precipitated after the boiling water treatment. The appearance quality of the plate samples prepared by using the lubricants of Comparative Examples 1 to 5 also meets the requirements of the national standards, but the plate prepared by using the lubricant of Comparative Example 2 has a slight surface frosting problem after the boiling water treatment, and the boiling water resistance is slightly insufficient.
[0046] It can be seen that the lubricating material of the present application is used in the preparation of PP wood-plastic composite boards, and the prepared boards have excellent appearance quality and excellent boiling water resistance.
[0047] 2) Comprehensive physical properties According to the method described in GB∕T 24508-2020, the static bending strength, elastic modulus, water absorption rate and fungal corrosion weight loss rate of the plate were tested; according to the method described in GB / T 13520-1992, the impact strength of the plate was tested. The test results are shown in Table 3 below.
[0048] Table 3 Performance test 2) Results Static bending strength (MPa) Elastic modulus (MPa) Water absorption (%) Impact strength (kJ / m2) Sample 1 21.8 2948 <1 8.92 Sample 2 22.1 3011 <1 9.04 Sample 3 21.9 2996 <1 9.01 Sample 4 22.4 3058 <1 9.11 Sample 5 22.5 3066 <1 9.12 Sample 6 22.5 3063 <1 9.12 Sample 7 22.7 3082 <1 9.13 Sample 8 22.7 3079 <1 9.13 Sample 9 23.4 3268 <1 9.27 Sample 10 23.3 3259 <1 9.27 Comparative sample 1 16.2 1844 <1 4.42 Comparative sample 2 15.9 1897 <1 4.68 Comparative sample 3 15.4 1672 <1 3.76 Comparative sample 4 17.1 2406 <1 6.24 Comparative sample 5 16.4 2148 <1 5.96 It can be seen from the data in Table 3 that the mechanical properties of the boards of samples 1 to 10 of the present application are better than those of the boards of comparative samples 1 to 5. It can be seen that the use of the lubricant of the present application can effectively improve the compatibility between PP and wood powder, and can also effectively enhance the mechanical properties of the prepared boards.
[0049] From the data comparison of sample 10 and comparative samples 3 to 5 in Table 3, it can be seen that after the specific modified bamboo fiber powder is introduced in this application, the mechanical properties of the prepared board are significantly improved. Compared with the pure lubricating component lubricant and the lubricant with alkali-treated bamboo fiber powder, the performance improvement is very obvious; in addition, in the lubricant ratio of this application, the grafting rate of maleic anhydride grafted polyethylene has a greater impact on this application, and the grafting rate needs to be controlled at about 0.5%. The use of raw materials with a higher grafting rate will lead to a decrease in board performance. The applicant speculates that this is because the lubricant of this application adds wood components. Although the maleic anhydride grafted polyethylene with a higher grafting rate has a better interface modification effect, it is easy to undergo a cross-linking reaction with wood powder to form a local mesh structure, which will affect the dispersion of the modified bamboo fiber powder, thereby causing a decrease in performance.
[0050] By comparing the data of samples 1 to 10 in Table 3, it can be seen that the performance of samples 4 to 6 of the present application is slightly better than that of samples 1 to 3, and the performance of sample 9 is slightly better than that of samples 7 to 8. It can be seen that, based on the present application, by optimizing the ratio of the lubricant, a relatively better lubricant product can be obtained; and by optimizing the preparation process of the bamboo fiber powder, the whiskers of nano-silicon dioxide can be made denser, thereby better improving the lubrication effect.
[0051] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A lubricant for a wood-plastic composite material for a vehicle, characterized in that: The mass proportions of the raw material components of the lubricant are: 24-32 parts of maleic anhydride grafted polyethylene, 8-10 parts of silicone powder, 30-40 parts of nano-silicon dioxide in-situ modified bamboo fiber powder, and 20-40 parts of polypropylene wax; the particle size of the nano-silicon dioxide in-situ modified bamboo fiber powder is 80-200 meshes, and the grafting rate of the maleic anhydride grafted polyethylene is 0.4-0.6%.
2. The lubricant for the automotive wood-plastic composite material according to claim 1, characterized in that: The mass proportion of each raw material component of the lubricant is: 28-30 parts of maleic anhydride grafted polyethylene, 8-10 parts of silicone powder, 32-36 parts of nano-silicon dioxide in-situ modified bamboo fiber powder, and 28-30 parts of polypropylene wax.
3. The lubricant for the automotive wood-plastic composite material according to claim 1, characterized in that: The method for preparing the nano-silicon dioxide in-situ modified bamboo fiber powder comprises the following steps: S1-1, placing the original bamboo fiber powder in a sodium hydroxide solution with a concentration of 4-8%, soaking for more than 4 hours, filtering out the sodium hydroxide solution, washing the obtained original bamboo fiber powder with distilled water until there is no residual sodium hydroxide, and then placing it in a constant temperature drying oven to dry to constant weight, to obtain alkali-treated bamboo fiber powder; S1-2, treating the alkali-treated bamboo fiber powder obtained in step S1-1 by a sol-gel method to generate nano-silicon dioxide on its surface in situ, and then drying it in a constant temperature drying oven to constant weight to obtain nano-silicon dioxide in situ modified bamboo fiber powder.
4. The lubricant for the automotive wood-plastic composite material according to claim 3, characterized in that: In the step S1-1, the drying temperature is 80-100°C.
5. The lubricant for the wood-plastic composite material for vehicles according to claim 3, characterized in that: In the step S1-1, the dried alkali-treated bamboo fiber powder is further subjected to a pulverization treatment to disperse the agglomerated alkali-treated bamboo fiber powder.
6. The lubricant for the automotive wood-plastic composite material according to claim 3, characterized in that: In the step S1-2, the sol-gel treatment includes the following steps: first, preparing a reaction solution, mixing tetraethyl orthosilicate, methyltriethoxysilane, ethanol, acetic acid and water in a volume ratio of 1:1:1:0.01:0.1 to prepare a reaction solution; then, mixing the alkali-treated bamboo fiber powder with the reaction solution in a mass ratio of 1:10, ultrasonically dispersing, standing for 1 to 2 hours, filtering out and standing at room temperature for 3 to 5 days.
7. The lubricant for the automotive wood-plastic composite material according to claim 3, characterized in that: In step S1-2, the drying temperature is 120-125°C.
8. The method for preparing a lubricant for a wood-plastic composite material for a vehicle according to claim 1, characterized in that: The raw material components of the lubricant also include an antioxidant, and the added amount of the antioxidant is 1 to 3 parts.
9. A method for preparing a lubricant for a wood-plastic composite material for a vehicle according to claim 1, characterized in that: The following steps are involved: S1. According to the steps of claim 3, preparing nano-silicon dioxide in-situ modified bamboo fiber powder; S2. Accurately weigh the raw materials in the formula, place them in a high-speed mixer and stir and mix them thoroughly to obtain a mixture; S3, adding the mixed material obtained in step S2 into an extruder, and obtaining a lubricant for a wood-plastic composite material for a vehicle through extrusion and granulation.
10. The method for preparing a lubricant for a wood-plastic composite material for a vehicle according to claim 9, characterized in that: In step S3, the temperature of each section of the extruder is controlled within 165°C.